2004
DOI: 10.1002/fld.781
|View full text |Cite
|
Sign up to set email alerts
|

Large eddy simulations of turbulent swirling flows in a dump combustor: a sensitivity study

Abstract: SUMMARYLarge eddy simulations (LES) of conÿned turbulent swirling ows in a model dump combustor are carried out. The simulations are based on a high-order ÿnite di erence method on a Cartesian grid, with the sub-grid scale stress tensor modelled using a scale-similarity model. The aims of this work are to study the physics of the ow and to evaluate the performance of LES method for simulation of the major features of turbulent swirling ows-the vortex breakdown, the highly anisotropic and fast-decaying turbulen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 25 publications
2
16
0
1
Order By: Relevance
“…Similar effects of the outlet contraction on the vortex breakdown structures have been observed in a recent experimental study of swirling isothermal and reactive flows in a combustor geometry for higher Reynolds number turbulent flows [3]. In some other studies the outlet contraction has shown low impact on the flow structures in the main chamber under a condition that the swirl number is relatively low and the chamber length to diameter ratio is relatively large [4,5].…”
Section: Introductionsupporting
confidence: 55%
“…Similar effects of the outlet contraction on the vortex breakdown structures have been observed in a recent experimental study of swirling isothermal and reactive flows in a combustor geometry for higher Reynolds number turbulent flows [3]. In some other studies the outlet contraction has shown low impact on the flow structures in the main chamber under a condition that the swirl number is relatively low and the chamber length to diameter ratio is relatively large [4,5].…”
Section: Introductionsupporting
confidence: 55%
“…For example, Wang and Bai [89] performed LES calculations of non-reacting swirling flow fields and captured complex phenomena such as recirculation, VB and precessing motion. DiMare et al [19], Kim et al [42], and Mahesh et al [55] carried out LES of combustion and simulated set-ups like simplified aero-engines.…”
Section: Studies Of Vortex Breakdownmentioning
confidence: 99%
“…Running the auxiliary computation at the same time as the main calculation obviates these problem, but introduces its own programming problems. Additionally, if the flow conditions change (e.g., a different Reynolds number), then the library must be recomputed or rescaled; the latter can be shown to introduce additional problems into the simulation [5]. Integrating the auxiliary computation into the main domain in this manner, on the other hand, is much more elegant and easier to manage and generates extremely good mean and turbulent flow results.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of this approach include [3,4]. However, such approaches suffer problems related to the nonphysical nature of the turbulence introduced at the inlet, leading to incorrect prediction of turbulent kinetic energy and energy spectra downstream of the inlet [5].…”
mentioning
confidence: 99%
See 1 more Smart Citation